A Cross-sectional Study of Household Characteristic of WASH Facilities in West Java, Indonesia - Aulia Salmaddiina; Almira Nur Hanifah (Jurnal Presipitasi : Media Komunikasi dan Pengembangan Teknik Lingkungan, 2022)
Goal 6 of the SDGs goes beyond inadequate water, sanitation, and hygiene (WASH) access. In 2017, West Java's improved sanitation coverage was 64.4%, which is lower than Indonesia's average. The research objective is to investigate the correlation between household characteristics with WASH conditions in West Java. Data from the 2017 Indonesian DHS were used with 4,567 households. A cross-sectional study using logistic regression. The result showed an improved facility for WASH in West Java, respectively, source of drinking water (93.8%), sanitation facility (92.2%), handwashing facility (92.5%), and soap and water availability (95.7%). Based on data analysis, unimproved source of drinking water was associated with household age over 47 years (OR: 1.37, 95%CI 1.06-1.77), poor economic (OR: 6.14, 95% CI 4.12-9.15), and living in the rural area (OR: 4.63, 95% CI 3.56-6.03). Unimproved sanitation facilities, unimproved handwashing facilities, and unavailability of soap and water were associated with low education and poor economy.  At the same time, those living in rural areas are more likely to have unimproved handwashing facilities. It is recommended for the intervention program to focus more on characteristics that proved to be associated with the study.